2016
DOI: 10.11152/mu-866
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography as an integrated tool in clinical decision-making in the Emergency Department

Abstract: The aim of this retrospective study was to identify the role of ultrasonography as a decision-making and screening tool in emergency patients with pathological changes. Material and method: The study was carried out for 28 months in the Emergency Department of the County Emergency University Hospital, Cluj-Napoca. An ultrasound examination was performed as part of the clinical algorithm within the first hour of treating non-critical patients after they had been triaged. The diagnostic decision based on the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…In our institution, it was found that the most common US finding is gallstones. Similarly, a previous study in Romania showed that US is highly accurate in diagnosing cholelithiasis [30]. Several studies also noted that US is an efficient imaging modality in diagnosing gallbladder stones [16,17,31].…”
Section: Us Findingsmentioning
confidence: 70%
“…In our institution, it was found that the most common US finding is gallstones. Similarly, a previous study in Romania showed that US is highly accurate in diagnosing cholelithiasis [30]. Several studies also noted that US is an efficient imaging modality in diagnosing gallbladder stones [16,17,31].…”
Section: Us Findingsmentioning
confidence: 70%
“…70 Two smaller studies found similar accuracy of ultrasound in the same application. 71,72 Despite this, ultrasound remains the first-line modality for acute cholecystitis due to its widespread availability, minimal invasiveness, absence of radiation and cost-effectiveness. 7,8,[73][74][75] Clearly, comparing POCUS to a more accurate reference standard is likely to generate lower POCUS accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging, computed tomography and cholescintigraphy were all found to be more accurate than ultrasound in diagnosing acute cholecystitis in an earlier meta‐analysis, with ultrasound reported to have a sensitivity of 81% and a specificity of 83% 70 . Two smaller studies found similar accuracy of ultrasound in the same application 71,72 . Despite this, ultrasound remains the first‐line modality for acute cholecystitis due to its widespread availability, minimal invasiveness, absence of radiation and cost‐effectiveness 7,8,73–75 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ultrasonography is the most common initial imaging test in the evaluation of acute cholecystitis. However, the accuracy of ultrasonography alone is controversial [ [10] , [11] , [12] , [13] , [14] , [15] ], and its sensitivity ranges from 50 % to 95 % [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%